2021
DOI: 10.1787/1048819f-en
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for agricultural risk management policies

Abstract: Government support for agricultural risk management tools has grown substantially over the past two decades. While these tools can play a role in strengthening farm-level resilience by helping farmers to cope with the financial impact of adverse events, they also modify farmers' incentives to invest in riskreducing measures and market tools. Policy design is critical to maximise effectiveness while minimising unintended consequences. This report reviews the accumulated experience on four types of publiclysuppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Adaptation beyond field-level agronomic interventions could be necessary when farm-level resilience is exceeded. Compound extremes science can be more deeply integrated into new or redesigned insurance policies and products 194,200,210 , and into investments in income stabilization 210 and other in-kind support such as the dissemination of seeds and fertilizers following an extreme event. These risk reduction approaches might influence the decisions of farmers to invest in adaptive technologies and management options 210 .…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation beyond field-level agronomic interventions could be necessary when farm-level resilience is exceeded. Compound extremes science can be more deeply integrated into new or redesigned insurance policies and products 194,200,210 , and into investments in income stabilization 210 and other in-kind support such as the dissemination of seeds and fertilizers following an extreme event. These risk reduction approaches might influence the decisions of farmers to invest in adaptive technologies and management options 210 .…”
Section: Review Articlementioning
confidence: 99%
“…Compound extremes science can be more deeply integrated into new or redesigned insurance policies and products 194,200,210 , and into investments in income stabilization 210 and other in-kind support such as the dissemination of seeds and fertilizers following an extreme event. These risk reduction approaches might influence the decisions of farmers to invest in adaptive technologies and management options 210 . However, the availability of crop insurance does not always result in the adoption of climate-smart, conservation management practices 211,212 , and alternative management strategies (such as crop diversification 194 or precision agriculture techniques 213 ) might preferred to loss-limiting policies like crop insurance.…”
Section: Review Articlementioning
confidence: 99%
“…Glauber et al [66] found that "subsidized crop insurance has been criticized for distorting resource allocation decisions, with impacts on the environmental sustainability of the sector. As a result, .…”
Section: Discussionmentioning
confidence: 99%
“…Our research results are consistent with previous empirical findings in developed countries. Glauber et al [66] underlined that subsidized agricultural insurance (in particular, crop insurance) lead to several distortions (production choices and input use). The aforesaid distortions can cause some externalities affecting "the environment, climate, nutrition and trade".…”
Section: Discussionmentioning
confidence: 99%
“…Lack of self-protection can result in substantial public expenditures. For instance, the OECD countries paid over €3 billion for agricultural disaster relief in response to natural disasters in 2017-2019(OECD, 2020. If the policy-makers want to improve the risk management policies and predict their impact, it is crucial for them to understand what motivates farmers to protect themselves against low-probability weather shocks.…”
Section: Introductionmentioning
confidence: 99%